Using data about accepted and rejected articles in the Journal of Dental Education to increase authors' chances of article acceptance. Issue 8 (30th March 2022) - Nalliah, Romesh P.; Kimner, Sue; Reddy, Michael
Abstract: Purpose/objectives: The purpose of our study was to identify trends and compare keywords from titles and methods among articles accepted and rejected for publication in the Journal of Dental Education (JDE). Methods: The titles and abstracts of JDE articles submitted between 2010 and 2020 were extracted. We studied the frequencies of keywords in the title and abstracts and used simple descriptive data to present the information. Additionally, keywords from the methods section from JDE articles reviewed between 2015 and 2020 were analyzed by acceptance versus rejection. University of Michigan Medical School's committee on human subject studies provided an exemption (HUM00196884). Results: Articles with the terms "knowledge, " "skills, " and "attitudes" appear, separately or together, in the titles of submissions to JDE 510 times during the study period—190 in accepted articles and 320 in rejected articles (an acceptance rate of 37.3%). The term "clinical" is in the title of 337 articles submitted to JDE—195 accepted and 142 rejected (an acceptance rate of 57.9%). However, the term "pre‐clinical" is associated with only 56 articles in the last 10 years—36 accepts and 20 rejects (64.3%). Studies with cross‐sectional study design were accepted at a rate of 72.0% and manuscripts with cohort study designs were accepted at 53.3%. Systematic reviews were accepted at 44.4%, surveys were accepted at 36.7%, meta analyses were accepted at 28%. Questionnaires were accepted at 14%. Conclusions: Higher quality study designs were more likely to be accepted for publication. Studies including a randomizing process and studies that were longitudinal in nature were more likely to be accepted for publication.